Development of an Integrated Science Module of the Quran on the Subject Material of the Human Circulation System to Grow Religious Attitude of Students of Class VIII MTS - Rosita Maulidan; Adi Fadli; Mukminah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the validity, response of students and know the integrated science module the human circulatory system as it relates to the Qur'an can foster religious attitudes of class VIII MTs. Development research using the Four D model developed by Thiagrajan. The findings of this research demonstrated that the integrated science module of the Qur'an on the subject matter of the human circulatory system obtained a percentage result of 73% from material experts with the